WATER RESOURCES OF SUGAPA INTAN JAYA - PAPUA DISTRICT - Puji Pratiknyo (Universitas Pembangunan Nasional Veteran Yogayakarta, 2020)
The existence and potential of water resources in the Sugapa District need to be known because the Sugapa District is the capital of Intan Jaya Regency. By conducting geological mapping and research as well as direct measurement of quantity and quality in the field, the results are obtained that springs are the main water resource used by residents in the study area. There are 7 (seven) springs in the Sugapa District which are in difficult morphology, in the form of steep valleys at high elevation (1,749 - 2,273 meters from sea level). Spring water discharge varies (<0.1 - 5.78 liters / second) with a quality that in general the parameters meet the drinking water quality requirements.